PEMANFAATAN APLIKASI SMARTPHONE SEBAGAI MEDIA PENGHASIL UANG - Sofyan Mufti Prasetiyo; Iqbal Fahrozi; Nandar Rustandar; Bagas Gemilang Ryadi (CV. Multi Kreasi Media, 2023)
Smartphones are a communication tool that is often used today, ranging from children, teenagers, adults, and the elderly. At first, cellphones were only for communication, with the development of the technological era so that they could send data and add applications they liked, the use of communication media is a basic need for individuals, groups, and organizations. At this time, the role of cellphones has become a primary daily need. Especially since the Covid-19 pandemic and the enactment of social distancing which was later renamed to physical distancing which resulted in all activities being carried out online or in networks, especially schools temporarily closed and online learning through digital media. The problems that have arisen in Muara Lingkar Village since the Covid-19 pandemic, namely: (1) The lack of understanding of technology issues which of course, if utilized can produce a better economy (2) The lack of public knowledge, especially parents of teenagers in the Muara Karang village, about online schooling ( 3) Teenagers still can't use smartphones as a field to make money in positive terms. Teenagers know that smartphones are only used for playing games, calling, WhatsApp, Facebook which plays games and others that require internet quota, Muara village among those with internet signals only Telkomsel cards where the internet quota is expensive, and will affect parents whose income is not much, and surely teenagers if their internet quota runs out ask their parents for money with the excuse of buying internet quota to study online even though their internet quota is mostly used for playing games and others. The solution to this problem is to introduce youth to knowledge of technological issues that are capable of producing a good economy. This activity is carried out face-to-face (on the spot training) using the method of delivering socialization material by introducing, conveying and learning techniques. The results of the activities of the youth added knowledge about the benefits and tips for using smartphones and technology especially for making money.